Emergent transcatheter mitral valve‐in‐valve implantation in a patient with cardiogenic shock secondary to a failed mitral bioprosthesis. Issue 7 (27th May 2015) - Alli, Oluseun; Booker, Oscar; Davies, James
Abstract : Transcatheter valve‐in‐valve (VIV) implantation is emerging as a therapeutic option for treatment of failed bioprosthesis in patients that are deemed high‐risk or inoperable for redo‐valve replacement. It can be carried out in suitable bioprosthetic valves in any position and usually performed as an elective or semi‐elective procedure. Here, we report a case of emergent transcatheter VIV implantation in a failed mitral bioprosthesis in a critically ill patient with cardiogenic shock. We conclude that transcatheter VIV implantation may also be an option for critically ill patients with failing bioprosthesis. © 2015 Wiley Periodicals, Inc.